LXA4 Inhibits Lipopolysaccharide-Induced Inflammatory Cell Accumulation by Resident Macrophages in Mice - Mei HX (Dove Medical Press, 2021)
Hong-Xia Mei, Yang Ye, Hao-Ran Xu, Shu-Yang Xiang, Qian Yang, Hong-Yu Ma, Sheng-Wei Jin, Qian Wang Department of Anesthesia and Critical Care, The Second Afﬁliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325027, People’s Republic of ChinaCorrespondence: Sheng-Wei Jin; Qian WangDepartment of Anesthesia and Critical Care, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, 109 Xueyuan Road, Wenzhou, Zhejiang Province, 325027, People’s Republic of ChinaTel +86-577-88002806Fax +86-577-88832693Email jinshengwei69@163.com; wqian84@163.comIntroduction: Alveolar macrophages that regulate the inflammatory response in lungs are the main target cell for the treatment of inflammatory pulmonary pathologies, such as acute respiratory distress syndrome (ARDS). Yolk sac derived alveolar resident macrophages play an important role in the pulmonary inflammatory response. With regards to anti-inflammatory actions, lipoxin A4 (LXA4) has been identified as an inflammatory “braking signal”.Methods: In vivo, LXA4 (0.1 μg/mouse) was injected intraperitoneally after intratracheal (1 mg/kg) lipopolysaccharide (LPS) administration; flow cytometry was used to measure peripheral blood monocyte derived recruited macrophage and neutrophil numbers; resident alveolar macrophage was depleted by liposome clodronate; CXCL2, CCL2, MMP9 level was detected by RT-PCR and ELISA. In vitro, sorted resident macrophages (1× 106) were cultured with LPS (1 μg/mL) and LXA4 (100 nmol/mL) with or without BOC-2 (10 μM) for 24 h to gain a better understanding of the mechanisms of LXA4.Results: LXA4 inhibited tumor necrosis factor-a (TNF-a) and interleukin-1β (IL-1β) production induced by LPS. LXA4 also mediated LPS-induced macrophage recruitment and showed that this was dependent on CCL2 secretion and release by resident macrophages. LXA4 protects lung tissue by inhibiting neutrophil recruitment, partly through the CXCL2/MMP-9 signaling pathway. CXCL2 and MMP-9 are mainly expressed by resident macrophages and neutrophils, respectively. Finally, LXA4’s beneficial effects were abrogated by BOC-2, an LXA4 receptor inhibitor.Conclusion: These results suggest that LXA4 may be a promising therapy for preventing and treating ARDS.Keywords: resident macrophage, recruited macrophage, neutrophil, lipoxin A4, lipopolysaccharide